PLANET 50:50, SOCIAL CAPITAL, AND PORTRAITS THE ROAD OF BENGKULU WOMEN TOWARD THE NATIONAL PARLIAMENT - Syafuan Rozi; Dewi Coryati; M.Fadhil Nurdin; Wahyu Gunawan; Margo Purnomo (Pusat Riset Politik BRIN, 2023)
This study attempts to inspect the issue of gender politics in Indonesia, focusing on the electoral struggle of female legislative candidates in the region of Bengkulu. The UN’s program, Planet 50:50, will be taken into account in gauging the extent of these candidates’ success amidst the predominantly patriarchal culture across three elections (2009, 2014, 2019)... Being a qualitative study based on discourse analysis, this study will primarily employ the concept of social capital by Pierre Bordeau (1986) and David Putnam (1993). Among the significant findings are: first, in addition to building a primordial network of religious and ethnic organizations as every Indonesian legislative candidate commonly does, female national parliament candidates in Bengkulu must work harder to create community empowerment to gain more public trust and establish the norm that women are genuinely fit and capable for election and re-election. Second, community empowerment is performed via various programs for first-time voters, youth, women, educators, and farmers; in addition to utilization of different media to promote tourism and market products. This study, hopefully, may enrich pre-existing discourse on gender and politics by juxtaposing its local practices with the ideals encapsulated in the SDG target that is Planet 50:50.